A microbial fuel cell system with manganese dioxide/titanium dioxide/graphitic carbon nitride coated granular activated carbon cathode successfully treated organic acids industrial wastewater with residual nitric acid. (May 2020) - Zhang, Qian; Liu, Lifen
Graphical abstract: Highlights: The prepared MnO2 /TiO2 /g-C3 N4 @GAC had great electro-catalytic properties. A MFC with the above cathode efficiently removed COD, NH4 ± -N and NO3 − -N. The COD removal capacity was 17.77 kg COD m −3 d −1 . Proteobacteria was dominant in MFC anode. Abstract: To meet the urgent demands for sustainable and efficient, environmental-friendly wastewater treatment, a Microbial fuel cell reactor system with MnO2 /TiO2 /g-C3 N4 (manganese dioxide/ titanium dioxide/graphitic carbon nitride) @GAC (granular activated carbon) electrode was developed. It was both efficient and energy-saving in treating organic acid wastewater generated in Nylon production, with high-concentration COD and residual nitric acid. The MnO2 /TiO2 /g-C3 N4 catalyst was deposited on GAC via in-situ growth and sol-gel method. The COD, NH4 + -N and NO3 − -N was efficiently removed (respectively 98%, 99% and 99%). The COD removal capacity (17.77 kg COD m −3 d −1 ) and the maximum power density (1176.47 mW m −3 ) was respectively 36.83% and 65.29% higher than the GAC cathode system. The anodic and cathodic microbial consortiums in MFC were analyzed and compared. The MnO2 /TiO2 /g-C3 N4 @GAC MFC system is technically feasible and cost-effective in treating industrial wastewater.